Phytochemical Screening, Activity Antioxidant and Activity Test of Antimicrobials Ethanol Extract of Gagatan Harimau Leaves (Paraboea leuserensis B.L Burtt) - Ade Putrianti Marbun; Dwi Suryanto; Elimasni (Jurnal Penelitian Pendidikan IPA, 2024)
Paraboea leuserensis BL Burtt, a plant endemic to the provinces of Aceh and North Sumatra, is traditionally used for medicinal purposes by chewing or boiling, treating conditions such as stomach aches and increasing stamina. Research This aiming to know difference activity antioxidant and antimicrobial from extract ethanol gagatan harimau leaves. Extraction was carried out using the maceration method using ethanol solvent. Phytochemical testing includes tests alkanoids, flavonoids, glycosides, saponins, tannins, steroids and triterpenoids. Antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picryl hydrazyl) method which was measured at a wavelength of 515 nm and antibacterial activity test by disc diffusion method (Kirby-Bauer Test). Test results phytochemicals show metabolit secondary contained​ in extract ethanol leaf idea tiger among them alkaloids, flavonoids, glycosides, saponins, tannins, and steroids/triterpenoids. Extract ethanol gagatan harimau leaf own activity antioxidants that are classified as strong based on IC50 value obtained​ as big as 45.95 ppm Activity test antimicrobial In E. coli inhibition zone value highest at concentrations of 75%, and 50%., S. aureus mark the highest inhibition zone at concentrations of 75% and 50%, then in C. albicans with inhibition zone values at concentrations of 75% and 50%.